Why and to what extent are global forces leading to a convergence in public policies (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
The study of cross-national policy convergence is at the centre of political science research. This trendis linked to an increased interest in globalization and in the domestic impact of European integration. Thepaper provides a comparative study of responses of the United Kingdom and France to the common stimulusof structural changes in the telecommunication industry. During the 1980- 1998s these two countriesimplemented liberalisation and privatisation policies. It will examine how the similarities in outcomes anddifferences in the process can be explained. The paper will try to find answers for the following question:how do global forces direct policy convergence? To what extent do countries respond for these forces?Does the strong growth of economic and institutional interrelationship between countries lead to increasinglysimilar policies across countries? What explains the implementation of similar policies across countries?Under which circumstances can we expect that domestic policies converge or diverge?